2015
DOI: 10.1182/blood-2014-12-618470
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CLL exosomes reveals a distinct microRNA signature and enhanced secretion by activation of BCR signaling

Abstract: Key Points• CLL exosomes exhibit a disease-relevant microRNA signature.• B-cell receptor signaling enhances exosome secretion in CLL that can be antagonized by ibrutinib.Multiple studies show that chronic lymphocytic leukemia (CLL) cells are heavily dependent on their microenvironment for survival. Communication between CLL cells and the microenvironment is mediated through direct cell contact, soluble factors, and extracellular vesicles. Exosomes are small particles enclosed with lipids, proteins, and small R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
152
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(159 citation statements)
references
References 67 publications
5
152
1
1
Order By: Relevance
“…Recently, it was demonstrated that EVs derived from BM MSCs facilitated the progression of multiple myeloma, 44 and those derived from CML and chronic lymphocytic leukemia cells facilitated the progression through an autocrine mechanism. 19,21 Moreover, primary AML cells released EVs which were possibly enriched for both coding and non-coding RNAs. 17,45 These findings led us to explore the possibility of EVs-mediated communication between leukemic cells and MSCs.…”
Section: A B Cmentioning
confidence: 99%
“…Recently, it was demonstrated that EVs derived from BM MSCs facilitated the progression of multiple myeloma, 44 and those derived from CML and chronic lymphocytic leukemia cells facilitated the progression through an autocrine mechanism. 19,21 Moreover, primary AML cells released EVs which were possibly enriched for both coding and non-coding RNAs. 17,45 These findings led us to explore the possibility of EVs-mediated communication between leukemic cells and MSCs.…”
Section: A B Cmentioning
confidence: 99%
“…3 Recently the relevance of extracellular vesicles (EV) to the intercellular cross-talk and the establishment of a tumor-promoting CLL microenvironment was investigated in several studies. [4][5][6][7] EV are either shed from the cell surface or released as exosomes via exocytosis upon generation in multivesicular bodies. Tumor cell-derived EV enable the transfer of cancer-associated proteins and RNA which are able to alter the phenotype Supplementary Table S1A for the patients' characteristics).…”
Section: Letters To the Editormentioning
confidence: 99%
“…This contributes to increasing evidence that the ability of tumor cells to induce CAFs is a universal feature of progression in both solid 8 and blood 7,10 cancers. These data also provide incentive for detailed mechanistic investigation of the role exosomes play in pathogenic signaling processes 6 and regulating the understudied CLL-TME. Examining the contribution of exosomes and their content in predicting response (biomarkers) to different therapeutic agents including newly targeted kinase inhibitors will be of interest.…”
Section: Ll Is Characterized By An Accumulation Of Monoclonal Cd5mentioning
confidence: 99%
“…Proplatelet formation and maturation are heavily dependent on the membrane and cytoplasmic skeletal machinery, which include microtubule, actin, and spectrin. 5,6 Although microtubules and actin function as engines to power platelet formation and elongation, spectrin is necessary for the ultimate shape changes that occur when proplatelets mature For personal use only. on May 10, 2018. by guest www.bloodjournal.org From…”
Section: Ll Is Characterized By An Accumulation Of Monoclonal Cd5mentioning
confidence: 99%
See 1 more Smart Citation